Efeitos da cinesioterapia domiciliar na reabilitação de idosa com fratura proximal de úmero: relato de caso clínico - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá, 2026)
Introduction: Proximal humerus fractures are common among the elderly population and are associated with pain, functional limitations, and reduced independence, particularly when resulting from falls or trauma. Conservative treatment combined with physical therapy has proven to be an effective approach, with home-based kinesiotherapy standing out as a relevant strategy due to its potential to enhance treatment adherence and ensure continuity of rehabilitation. Objective: To analyze the effects of home-based kinesiotherapeutic rehabilitation on the functional recovery of an elderly patient with a proximal humerus fracture. Methods: This is a case report of an elderly patient with a non-displaced left proximal humerus fracture who received home-based treatment for 12 weeks, with sessions conducted three times per week. Assessments included the Visual Analog Scale (VAS), goniometry, the Medical Research Council (MRC) scale, the Disabilities of the Arm, Shoulder and Hand (DASH) questionnaire, and the Mini-Mental State Examination (MMSE). The physiotherapeutic protocol was divided into phases and included joint mobilization, stretching, active and resisted exercises, scapular control, and functional training. Results: A reduction in pain, progressive improvement in range of motion, and increased muscle strength of the affected upper limb were observed. Shoulder flexion improved from 90° to 140°, and abduction from 82° to 145°, with muscle strength gains from grade 3 to 4 on the MRC scale. The DASH score decreased from 91.67 to 69.38 points, indicating moderate functional improvement. Despite cognitive impairment identified by the MMSE, the patient demonstrated significant functional progress throughout treatment. Conclusion: Home-based kinesiotherapy proved effective in promoting functional recovery in the elderly patient with a proximal humerus fracture, improving mobility, muscle strength, and upper limb functionality. These findings reinforce the relevance of home-based physical therapy as a viable and safe alternative in the conservative management of such fractures in older adults, especially in the presence of functional limitations and mobility restrictions.
Keywords: Fratura de Úmero Proximal; Cinesioterapia; Reabilitação Domiciliar; CNPQ::CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL; ODS 3 – Saúde e bem-estar; ODS 10 – Redução das desigualdades